IMPLEMENTASI HARDENING SERVER LINUX UNTUK MENGURANGI RISIKO SERANGAN SIBER - Rakhmadi Rahman; Moh. Farel; Muhammad Dirga Sopan (CV. Denasya Smart Publisher, 2026)
Ubuntu 22.04 LTS Linux servers running default configurations are highly vulnerable to cyber threats including ransomware, cryptojacking, and SSH brute force attacks due to 22+ unnecessary open ports, active root login, and weak password authentication on standard port 22. This research implements systematic hardening through Agile Development methodology comprising 4 iterative phases (assessment, implementation, testing, audit) following CIS Ubuntu Linux Benchmark v2.0.0 guidelines. Results demonstrate Lynis security score improvement from 40/100 (medium risk) to 85/100 (good) representing +112.5% enhancement, 86.4% attack surface reduction (22→3 essential ports: SSH 2222, HTTP 80, HTTPS 443), and complete elimination of critical vulnerabilities. Brute force testing using Hydra (1000 attempts) achieved 95% mitigation within <30 seconds through Fail2Ban automated IP blocking via iptables rules. Defense-in-depth architecture comprises UFW default-deny firewall policy, SSH RSA 4096-bit key authentication, AIDE file integrity monitoring, and automated Lynis auditing via cron jobs. The implementation produces production-ready hardened servers with high availability, replicable Standard Operating Procedures (SOP), and addresses Indonesian cybersecurity research literature gaps.